Pengaruh Good Corporate Governance dan Financial Distress Terhadap Pengungkapan Laporan Keberlanjutan - Puspitasari, Nurma; Prihatni, Rida; Yusuf, Muhammad (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this study is to ascertain how audit committee size, board of directors size, independent commissioner size, and financial distress affect the disclosure of sustainability reports. The companies in the infrastructure sector listed on the IDX between 2020 and 2022 are the subject of this study. Purposive sampling was utilized in this study to choose the sample according to predetermined standards. The panel regression approach is used to process the data. The findings indicated that the size of the audit committee significantly impacted sustainability report disclosure, the size of the board of directors had no bearing on sustainability report disclosure, the size of independent commissioners significantly impacted sustainability report disclosure, and financial distress had no bearing on sustainability report disclosure. The study's findings suggest that businesses should disclose more about sustainability because the topic will be brought up more and more in the future.